Pan-Influenza A Protection by Prime–Boost Vaccination with Cold-Adapted Live-Attenuated Influenza Vaccine in a Mouse Model - Jang, Yo Han; Kim, Joo Young; Byun, Young Ho; Son, Ahyun; Lee, Jeong-Yoon; Lee, Yoon Jae; Chang, Jun; Seong, Baik Lin (Frontiers in Immunology, 2018)
Influenza virus infections continually pose a major public health threat with seasonal epidemics and sporadic pandemics worldwide. While currently licensed influenza vaccines provide only strain-specific protection, antigenic drift and shift occasionally render the viruses resistant to the host immune responses, which highlight the need for a vaccine that provides broad protection against multiple subtypes. In this study, we suggest a vaccination strategy using cold-adapted, live attenuated influenza vaccines (CAIVs) to provide a broad, potent, and safe cross-protection covering antigenically distinct hemagglutinin (HA) groups 1 and 2 influenza viruses. Using a mouse model, we tested different prime–boost combinations of CAIVs for their ability to induce humoral and T-cell responses, and protective efficacy against H1 and H5 (HA group 1) as well as H3 and H7 (HA group 2) influenza viruses. Notably, even in the absence of antibody-mediated neutralizing activity or HA inhibitory activity in vitro, CAIVs provided a potent protection against heterologous and heterosubtypic lethal challenges in vivo. Heterologous combination of prime (H1)–boost (H5) vaccine strains showed the most potent cross-protection efficacy. In vivo depletion experiments demonstrated not only that T cells and natural killer cells contributed to the cross-protection, but also the involvement of antibody-dependent mechanisms for the cross-protection. Vaccination-induced antibodies did not enhance the infectivity of heterologous viruses, and prime vaccination did not interfere with neutralizing antibody generation by the boost vaccination, allaying vaccine safety concerns associated with heterogeneity between the vaccines and challenge strains. Our data show that CAIV-based strategy can serve as a simple but powerful option for developing a “truly” universal influenza vaccine providing pan-influenza A protection, which has not been achieved yet by other vaccine strategies. The promising results of potency, breadth, and safety demonstrated in the mouse model support further studies in higher animal models for clinical relevance.